Solving asymmetric link problems in WSNs using site Link Quality Estimators and dual-tree topology - Kanitpong Pengwon (2018)
© 2016 IEEE. Asymmetric link problem is one of unwanted behaviors that typically comes with low power radio link in wireless sensor network. This study presents a dual-tree topology to solve the asymmetric link problem. LQI (Link Quality Indication) is used to discriminate links for forming the proposed topology and increase link reliability. The topology consists of two trees instead of a single tree in the traditional fashion. An experimental network is practically deployed a building to prove the performance of the dual-tree topology. The network consists of a coordinator node and 15 regular nodes. The result shows that the dual-tree topology can reduce number of hops.